2008
DOI: 10.1038/ejhg.2008.178
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis of the ACVR1 gene in Italian patients affected with fibrodysplasia ossificans progressiva: confirmations and advancements

Abstract: Fibrodysplasia ossificans progressiva (FOP, MIM 135100) is a rare genetic disorder characterized by congenital great toe malformations and progressive heterotopic ossification transforming skeletal muscles and connective tissues to bone following a well-defined anatomic pattern of progression. Recently, FOP has been associated with a specific mutation of ACVR1, the gene coding for a bone morphogenetic protein type I receptor. The identification of ACVR1 as the causative gene for FOP now allows the genetic scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
68
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(71 citation statements)
references
References 33 publications
1
68
0
Order By: Relevance
“…Patients 1, 2, 3, 4, and 6 were previously described (8,25). Patient 5, never reported before, showed a classical FOP presentation with bilateral malformation of the great toes, cervical stiffness and first clinical manifestation at 6 years as ectopic ossification of a knee, first diagnosed as exostosis.…”
Section: Materials and Methods Patients And Diagnostic Criteriamentioning
confidence: 99%
“…Patients 1, 2, 3, 4, and 6 were previously described (8,25). Patient 5, never reported before, showed a classical FOP presentation with bilateral malformation of the great toes, cervical stiffness and first clinical manifestation at 6 years as ectopic ossification of a knee, first diagnosed as exostosis.…”
Section: Materials and Methods Patients And Diagnostic Criteriamentioning
confidence: 99%
“…This allele has also been identified in several countries including South Africa, Korea, Spain, Italy, and Turkey (Bocciardi et al, 2009;Lee et al, 2009;Dandara et al, 2012;Morales-Piga et al, 2012;Eresen Yazıcıoglu et al, 2013). Our identification of the c.617G>A; p.Arg206His allele in 12 individuals, combined with the previous report of three Indian patients (Shukla et al, 2013), suggests that in India most cases of FOP result from this allelic variant.…”
Section: Discussionmentioning
confidence: 57%
“…Korea, France, Italy, Brazil, Spain, South, Africa, India, Mexico, Egypt, Turkish, China, Germany (Lin et al, 2006), (Nakajima et al, 2007), , (Lucotte et al, 2008), (Bocciardi et al, 2009), (Carvalho et al, 2010), (Morales-Piga et al, 2012), (Dandara et al, 2012), (Shukla et al, 2013), (Herrera-Esparza et al, 2013), (Al-Haggar et al, 2013), (Eresen Yazıcıoglu et al, 2013), (Zhang et al, 2013), (Stefanova et al, 2012) (Connor & Evans, 1982), (Stefanova et al, 2012), (Carvalho et al, 2010) Exons 8 and 9 c.1067 G>A p.Gly356Asp Present Japan, Germany, China (Kaplan et al, 2009), 3 (Furuya et al, 2008), (Stefanova et al, 2012), (Zhang et al, 2013) Exon 9 c.1124 G>C p.Arg375Pro Absent Unspecified (Kaplan et al, 2009) …”
mentioning
confidence: 99%
“…Ratbi et al (2010) reported the case of a Moroccan patient with FOP carrying a rarely occurring mutation at c.774G>T of ACVR1 gene. Bocciardi et al (2009) reported the c.617G>A mutation, leading to the p.R206H substitution in the ACVR1 gene in 15 out of 17 Italian patients. In two patients, they found a novel mutation c.774G>C; p.R258S substitution (Bocciardi et al, 2009).…”
Section: Acvr1/alk2mentioning
confidence: 99%
“…Bocciardi et al (2009) reported the c.617G>A mutation, leading to the p.R206H substitution in the ACVR1 gene in 15 out of 17 Italian patients. In two patients, they found a novel mutation c.774G>C; p.R258S substitution (Bocciardi et al, 2009). Furuya et al (2008) reported a 62-year-old man with slowly progressive FOP, and bearing a novel mutation in ACVR1.…”
Section: Acvr1/alk2mentioning
confidence: 99%